Life cycle assessment (LCA) for the production of palm biodiesel in Malaysia and Thailand - Norfaradila, J.; Norela, S.; Salmijah, S.; Ismail, B.S. (Penerbit Universiti Kebangsaan Malaysia, 2014)
Energy supply and its security issues have been a hot topic recently. Consequently, the search for alternative fuel sources is receiving much attention and biodiesel is one of the most promising where palm oil is the main feedstock for the industry.This present study compared the environmental impact resulting from the production of biodiesel in Malaysia and Thailand using the life cycle assessment method (LCA). Different scenarios that influenced the development of the biodiesel industry in the two countries were the main focus of the study. Malaysia as the world’s second largest producer and exporter of palm oil and the initiatives taken by the Thai government have greatly influenced the development of the industry. The LCA includes the phase of raw material extraction (oil palm cultivation, fresh fruit bunch processing and refining of crude palm oil), and the biodiesel processing phase (transesterification process). The functional unit was the production of 1 metric tonne of biodiesel, and the life cycle impact assessment (LCIA) was determined using the SimaPro 7.2 software through the Ecoindicator 99 method. LCIA showed that the production of biodiesel in Thailand recorded higher impact values (2.53 10-3 DALY for human health, 109.20 PDFm2 yr for ecosystem quality and 3497 MJ surplus for resource depletion) compared to those of Malaysia (6.89.10-4 DALY, 34.87 PDFm2 yr and 1628 MJ surplus). The use of higher quantities of fertilizers and pesticides for the oil plam cultivation process in Thailand influenced the impact values obtained compared to those in Malaysia.